3D axial and circumferential wall shear stress from 4D flow MRI data using a finite element method and a laplacian approach. Issue 5 (4th October 2017) - Sotelo, Julio; Dux‐Santoy, Lydia; Guala, Andrea; Rodríguez‐Palomares, José; Evangelista, Arturo; Sing‐Long, Carlos; Urbina, Jesús; Mura, Joaquín; Hurtado, Daniel E.; Uribe, Sergio
Abstract : Purpose: To decompose the 3D wall shear stress (WSS) vector field into its axial (WSSA ) and circumferential (WSSC ) components using a Laplacian finite element approach. Methods: We validated our method with in silico experiments involving different geometries and a modified Poiseuille flow. We computed 3D maps of the WSS, WSSA, and WSSC using 4D flow MRI data obtained from 10 volunteers and 10 patients with bicuspid aortic valve (BAV). We compared our method with the centerline method. The mean value, standard deviation, root mean‐squared error, and Wilcoxon signed rank test are reported. Results: We obtained an error <0.05% processing analytical geometries. We found good agreement between our method and the modified Poiseuille flow for the WSS, WSSA, and WSSC . We found statistically significance differences between our method and a 3D centerline method. In BAV patients, we found a 220% significant increase in the WSSC in the ascending aorta with respect to volunteers. Conclusion: We developed a novel methodology to decompose the WSS vector in WSSA and WSSC in 3D domains, using 4D flow MRI data. Our method provides a more robust quantification of WSSA and WSSC in comparison with other reported methods. Magn Reson Med 79:2816–2823, 2018. © 2017 International Society for Magnetic Resonance in Medicine.